1987
DOI: 10.1007/bf01734837
|View full text |Cite
|
Sign up to set email alerts
|

Loss of fat, water, and protein during very low calorie diets and complete starvation

Abstract: The magnitude and composition of weight loss obtained in obese women on two forms of very low calorie protein-supplemented diets (Cambridge diet, Dresden drink) as well as by complete starvation has been investigated. With the VLCD, nitrogen equilibrium was reached on the 10th day of fasting, the cumulative nitrogen balance also being compensated. Nearly half of the body weight loss is due to loss of fat. In order to assess the benefit of fasting regimes, we propose to measure at least two parameters which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Clinical data. Earlier studies of changes in body composition of obese women during caloric restriction, using nitrogen balance and total body water measurements with tritiated water, showed that from day 10 and thereafter, nearly half of the body weight loss during VLCD is caused by loss of fat (26). The characteristics of the obese subjects before and during caloric restriction are shown in Tables 1 and 2.…”
Section: Methodological Experimentsmentioning
confidence: 99%
“…Clinical data. Earlier studies of changes in body composition of obese women during caloric restriction, using nitrogen balance and total body water measurements with tritiated water, showed that from day 10 and thereafter, nearly half of the body weight loss during VLCD is caused by loss of fat (26). The characteristics of the obese subjects before and during caloric restriction are shown in Tables 1 and 2.…”
Section: Methodological Experimentsmentioning
confidence: 99%
“…It is commonly assumed that the decline in body weight affects all body compartments with an ensuing general effect on various body functions. Studies on the mechanisms behind weight loss associated with starvation, semistarvation, tumor burden, cardiac cachexia, and liver cirrhosis [5][6][7][8][9][10] have shown a variety of changes in body composition; but because there have been few observations after gastrectomy [11] our primary aim was to obtain detailed information on the changes in body composition (fourcompartment model) occurring concomitantly with the weight loss that is a regular phenomenon during the first year after gastrectomy. Although the mechanisms behind this weight loss are multifactorial, one is most likely semistarvation due to impaired food intake [5,12,13].…”
mentioning
confidence: 99%
“…Studies on the mechanisms behind weight loss associated with starvation, semistarvation, tumor burden, cardiac cachexia, and liver cirrhosis [5][6][7][8][9][10] have shown a variety of changes in body composition; but because there have been few observations after gastrectomy [11] our primary aim was to obtain detailed information on the changes in body composition (fourcompartment model) occurring concomitantly with the weight loss that is a regular phenomenon during the first year after gastrectomy. Although the mechanisms behind this weight loss are multifactorial, one is most likely semistarvation due to impaired food intake [5,12,13]. Surgical interest has therefore focused on the significance of retaining or reconstructing a gastric reservoir after gastrectomy to counteract these adverse consequences, but clinical data so far have been contradictory.…”
mentioning
confidence: 99%
“…We performed additional measurements during the initial stages of fasting with VLED and during the initial stages of refeeding with conventional food. Different methods have shown that marked changes in body water compartments occur during this time (14,21,28). Thus, we hypothesized that greater discrepancy between the two methods potentially could occur at that point.…”
Section: Discussionmentioning
confidence: 97%
“…It has been well demonstrated that a profound natruresis and shifts in body water compartments occur during treatment especially with the beginning of a very-low-energy diet (VLED) and with the reintroduction of conventional food (14, 21,28). Because most methods for estimating FFM are based on specific assumptions about the hydration of tissues or body compartments, it is difficult to know how these measures are affected during these times.…”
Section: Introductionmentioning
confidence: 99%